2017
DOI: 10.4172/2165-7904.1000347
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between (binge) Eating and Identity Issues in Pre-bariatric Patients

Abstract: Obesity is associated with high levels of psychopathology, especially among those who engage in binge eating. Patients with binge eating also report poorer long term outcomes after bariatric surgery than patients without binge eating. However, the mechanisms underlying binge eating need further investigation. The present study investigates the relationship between identity issues and the functionality of (binge) eating behaviors in bariatric surgery candidates. Results showed that pre-bariatric patients who en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Several authors (Laghi, Baiocco, Liga, Lonigro, & Baumgartner, 2014;Schupak-Neuberg & Nemeroff, 1993;Wheeler et al, 2001) found that university students with binge eating reported more identity confusion and instability in one's self-concept compared with healthy controls. Finally, Boekaerts, Claes, Bouckaert, and Luyckx (2017) reported higher levels of identity confusion in prebariatric patients with binge eating compared with prebariatric patients without binge eating; no difference emerged for identity synthesis. Consequently, within the group of prebariatric patients, different subgroups may exist based on how these patients deal with identityrelated issues.…”
Section: Obesity and Identity Formationmentioning
confidence: 84%
“…Several authors (Laghi, Baiocco, Liga, Lonigro, & Baumgartner, 2014;Schupak-Neuberg & Nemeroff, 1993;Wheeler et al, 2001) found that university students with binge eating reported more identity confusion and instability in one's self-concept compared with healthy controls. Finally, Boekaerts, Claes, Bouckaert, and Luyckx (2017) reported higher levels of identity confusion in prebariatric patients with binge eating compared with prebariatric patients without binge eating; no difference emerged for identity synthesis. Consequently, within the group of prebariatric patients, different subgroups may exist based on how these patients deal with identityrelated issues.…”
Section: Obesity and Identity Formationmentioning
confidence: 84%